2015
DOI: 10.2139/ssrn.2635727
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Firm Cash Holdings on Monetary Policy

Abstract: Firm cash holdings increased substantially from 1980 to 2013. The overall distribution of …rm cash holdings changed in the same period. We study the implications of these changes for monetary policy. We use Compustat data and a model with …nancial frictions that allows the calculation of the monetary policy e¤ects according to the distribution of cash holdings. We …nd that the interest rate channel of the transmission of monetary policy has become more powerful, as the impact of monetary policy over real inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…The author observed that frequent monetary policy changes heighten uncertainties, which increases cash holding. Adao and Silva (2020) attribute the substantial increase in firm cash holdings from 1980 to 2017 in Europe to frequent changes in monetary policy and the effectiveness of interest rate channel due to increase in real interest rate.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…The author observed that frequent monetary policy changes heighten uncertainties, which increases cash holding. Adao and Silva (2020) attribute the substantial increase in firm cash holdings from 1980 to 2017 in Europe to frequent changes in monetary policy and the effectiveness of interest rate channel due to increase in real interest rate.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…Both European and U.S. companies have accumulated substantial cash reserves on their balance sheets. Corporate cash holdings corrected for inflation increased almost six times from 1980 to 2017, from 140 to 811 bn dollars (see Adao and Silva 2019). 1 Most recent data show that, for the main European countries (i.e., France, Germany, Italy and Spain) between 2007 and 2018, the aggregate nominal GDP and the stock of deposits held by non-financial firms increased by 16% and 90%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…1 This paper explores the relationship between firms' inflation expectations and their holdings of liquid assets. Curtis, Garin and Mehkari (2017) argue that the level of inflation is an important determinant of firm-level liquid asset holdings, and moreover, liquid asset holdings have increased in many countries in recent years (Adao and Silva, 2019). We expect that firms with higher shares of liquid assets should have more incentive to track and process information about inflation.…”
Section: Introductionmentioning
confidence: 96%